2022
DOI: 10.1109/access.2022.3152549
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Automated Log Analysis: A Systematic Literature Review and Mapping Study

Abstract: Logging is a common practice in software engineering to provide insights into working systems. The main uses of log files have always been failure identification and root cause analysis. In recent years, novel applications of logging have emerged that benefit from automated analysis of log files, for example, real-time monitoring of system health, understanding users' behavior, and extracting domain knowledge. Although nearly every software system produces log files, the biggest challenge in log analysis is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 275 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…They concluded that present log parsers are unsuitable for huge datasets, and the majority of them lack the requisite execution time efficiency. Korzeniowskiet al [20] conducted a systematic mapping study on the log analysis research. They presented their findings in the form of a landscape of automated log analysis, defining each discipline and highlighting recent research trends.…”
Section: Related Workmentioning
confidence: 99%
“…They concluded that present log parsers are unsuitable for huge datasets, and the majority of them lack the requisite execution time efficiency. Korzeniowskiet al [20] conducted a systematic mapping study on the log analysis research. They presented their findings in the form of a landscape of automated log analysis, defining each discipline and highlighting recent research trends.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, novel applications have emerged and it benefited from automated log-file analysis, for example, real-time monitoring of system health, understanding user behavior, and extracting domain knowledge. In [ 2 , 3 ], we can find a systematic review of recent literature (covering the period between 2000 and June 2021) related to automated log analysis. Application logs record the behavior of a system during its runtime, and their analysis can provide useful information.…”
Section: Related Workmentioning
confidence: 99%
“…The authors identify two specific types of interactions: composition (one service orchestrates a series of calls to other services) and substitution (service is called as part of an error-handling scenario after a failed call to another service). The authors assume the availability of IP address information in service logs, which (according to [1]) is true mostly for access logs and network logs that may not be available for applications other than web services. Additionally, basing the analysis on IP address correlation may be very challenging in cloudhosted applications, where services are replicated, and IP addresses can change dynamically.…”
Section: Related Workmentioning
confidence: 99%
“…Because of our focus on automation of knowledge discovery about systems, we are only interested in automated log analysis. According to [1], automated analysis of application logs is a widely studied discipline with growing interest among researchers in recent years. The most obvious usage of log analysis lies in the operations area (intrusion detection, monitoring) but its potential in reasoning about the business domain or the design of the software is also explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation